تفسیر احسن البیان کا بنیادی ماخذ( قرآن وسنت) سے استدلال کا جائزہ: Review of the Reasoning of Tafsir Ahsan Al-Bayan from its Primary Source (the Quran and Sunnah) (Al-Aasar, 2025)
This research paper explores the fundamental sources of Islamic jurisprudence, emphasizing the central role of the Qur’an and the Sunnah. Based on the interpretation of Tafseer Ahsan-ul-Bayan, it establishes the Qur’an as the primary source and foundation of divine law. The Sunnah of the Prophet Muhammad (ﷺ) is presented as the second source, providing practical explanation and clarification of the Qur’anic injunctions. The paper highlights the principles of derivation, authority, and application of Shariah rulings from these two sources.It concludes that the entire structure of Islamic law is firmly grounded upon these two divine sources — the Qur’an and the Sunnah.